2012
DOI: 10.1080/13854046.2011.640641
|View full text |Cite
|
Sign up to set email alerts
|

Interpreter-Mediated Neuropsychological Testing of Monolingual Spanish Speakers

Abstract: The primary objective of this study was to investigate empirically whether using an interpreter to conduct neuropsychological testing of monolingual Spanish speakers affects test scores. Participants included 40 neurologically normal Spanish-speakers with limited English proficiency, ages 18–65 years (M= 39.7, SD =13.9), who completed the Vocabulary, Similarities, Block Design, and Matrix Reasoning subtests of the Wechsler Adult Intelligence Scale-III in two counterbalanced conditions: with and without an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Using interpreters during the assessment only partially eliminates the language barrier. According to the literature, interpreters’ lack of experience in dementia assessment [ 31 , 51 , 52 ] and the lack of culturally and linguistically adapted assessment tools can complicate the whole process [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using interpreters during the assessment only partially eliminates the language barrier. According to the literature, interpreters’ lack of experience in dementia assessment [ 31 , 51 , 52 ] and the lack of culturally and linguistically adapted assessment tools can complicate the whole process [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants described various barriers, such as difficulties in communication and therefore also in assessment of cognitive impairment in persons with diverse linguistic and cultural backgrounds. As frequently reported in the literature [ 55 57 ], the need for interpreters further complicated assessments because they often lack competence in interpretation in assessment situations and may change sentences or their meaning to facilitate the translation.…”
Section: Discussionmentioning
confidence: 99%
“…Approach to the patients who seek care shall need a good understanding and trust between the victim and health care provider, safe environment, several interviews and overcoming the barriers (language and cultural). 35,36,37 It has been shown that in the presence of culturally competent people [36][37][38] and professional interpreter [39][40][41] the chance of getting details information are more than when there is no interpreter or there was a non-professional interpreter 42…”
Section: How To Approach?mentioning
confidence: 99%